HUBUNGAN KOMUNIKASI TERAPEUTIK TERHADAP KECEMASAN PASIEN PRE OPERASI SECTIO CAESAREA DI RUMAH SAKIT UMUM DAERAH MUNA BARAT - Sumarni, Sitti; Hamdiyah, Hamdiyah; Refu, Fikma Wati; Rustam, Husnul Khotimah; Sukarta, Asmah (Jurnal Kesehatan, 2025)
Communication is a key element in midwifery care, especially in building patient trust and comfort. Therapeutic communication plays a crucial role in helping patients manage anxiety, particularly when facing medical procedures such as surgery. This study aimed to evaluate the relationship between therapeutic communication provided by midwives and the level of patient anxiety before undergoing cesarean section (CS). This quantitative study utilized a cross-sectional design, involving 34 pre-operative CS patients selected using an accidental sampling method. Data were collected using questionnaires to assess the quality of therapeutic communication and the patient's anxiety levels. Univariate results indicated that the majority of midwives provided therapeutic communication of "good" quality (82.4%), and most patients did not experience anxiety (61.8%). Statistical tests showed a significant relationship between therapeutic communication and anxiety reduction (P-Value = 0.001). In conclusion, well-implemented therapeutic communication can significantly reduce anxiety in pre-operative CS patients. Therefore, it is highly recommended that training in empathetic and effective therapeutic communication continues to be enhanced as part of quality midwifery services.